North Carolina medical journal - Johnson, Wingate M. (Wingate Memory), 1885-1963 (Medical Society of the State of North Carolina, 1940)
Includes Transactions of the auxiliary to the Medical Society of the State of North Carolina and Proceedings of the North Carolina Public Health Association.